O mosaico cultural nas crônicas de Hernando del Pulgar e Andrés Bernáldez - Luna, Nathalia Martins (2024)
The aim of this paper is to analyze the cultural and religious formation of Jews, Muslims and Christians in Spain under the rule of the Catholic Monarchs in the 15th century. The central problem of the discussion presented was how these three religious segments structured themselves, shared definitions and religious symbolisms and cultural exchanges within a hostile environment marked by the regency and implementation of the Catholic Kings' unification project within Hispanic territory. The sources used were the chronicles "Crónica de los señores reyes católicos don Fernando y Doña Isabel de Castilla y de Aragon" by Hernando del Pulgar and "Historia de los Reyes Católi-cos don Fernando y doña Isabel" by Andrés Bernáldez. This explored the various actions of resistance by Jews and Muslims, the policies of institutional control and spatial and socio-cultural segregation provided by the crown, together with an understanding of the War of Granada (1492) as a basic point for changing laws and expelling those who professed the Islamic faith from Ibero-Hispanic territory. Comparative methodology was used, dialoguing with Cultural and Global History, in order to explore concepts such as "cultural exchanges", identities and "Cultural Mosaic". Therefore, it was of the utmost importance to investigate this cultural connection through a critical eye in order to understand the geographical symbolisms.